Lectin histochemistry assay in colon tissues for inter-species characterization - Moghaddam, Faezeh Yazdani; Darvish, Jamshid; Shahri, Nasser Mahdavi; Abdulamir, Ahmed Sahib; Daud, Siti Khalijah (Science Publications, 2009)
Problem statement: The digestive tract of animals including rodents has taxonomic and ecologic importance due to its ability in adaptation for different environments. Whereas colon absorbs water and carbohydrates, it has a vital role ecologically and physiologically and enjoys different histological structures in different rodents with various diets. Approach: Different rodent specimens belong to the family Muridae, namely Gerbilinae subfamily (Jerbillus nanus, Meriones Persicus, Meriones lybicus) Microtinae (Microtus, transcaspicus, Ellobius fascocapillus, Microtus sp.) Dipodidae (Alactage elater, Jucullus blanfordi) and scuridae (Funambulus penantii, spermophillus folvus), were studied via histochemistry techniques. Various parts of the digestive tract were removed and measured. Proximal colon was cut into 2-3 cm segments and fixed by bouin solution. The segments stained by lectin (PNA, WGA) chemochemistry. Results: Microscopic observations indicated that there were remarkable distinctions in the carbohydrates and glycoproteins content of the different layers of colon among different species of rodents. Both PNA and WGA lectin histochemistry showed high and significant discriminatory power among the studied species of rodents especially lectin staining in mucosal and absorptive cells (p<0.05). Goblet and epithelial cells showed much lower affinity to lectins. Conclusion: It was concluded that use of lectin histochemistry was a valid method for phylogenic characterization of rodents, may be other animals, depending on colon tissues. Moreover, Colon tissues proved to be highly distinct and variable among species of animals. This assay can also be used in determining the diet nature, geographical variation, diseases affection on different species of animals.